1999
DOI: 10.1557/proc-556-977
|View full text |Cite
|
Sign up to set email alerts
|

Sectrophotometric Investigation of U(VI) Chloride Complexation in the Naci/NaClO4 system

Abstract: Post closure radioactive release scenarios from geologic salt formation, such as the WIPP (Waste Isolation Pilot Plant) (USA) include hydrologic transport of radionuclides through a chloride saturated aquifer. Consequently, the understanding of actinide solution chemistry in brines is essential for modeling requiring accurate knowledge of the interaction between AnO22+ and chloride ions. Complexation constants of two U(VI) chloride species UO2Cl+ and UO2Cl20 have been intensively studied for about 40 years usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Such chloro complexes in ionic liquids may have some importance for the reprocessing by partitioning and further transmutation of highly radioactive waste . Several experimental and theoretical attempts have been made to reveal U(VI) chloro complexes with higher coordination numbers than those provided in the thermodynamic database. In aqueous solution up to three U(VI) chloro complexes, [UO 2 Cl] + , [UO 2 Cl 2 ] 0 , and [UO 2 Cl 3 ] − , have been observed by EXAFS (extended X-ray absorption fine structure) and UV–vis spectroscopy. Nguyen-Trung et al indentified the species [UO 2 Cl] + , [UO 2 Cl 2 ] 0 , [UO 2 Cl] 3− , [UO 2 Cl 4 ] 2− , and [UO 2 Cl 5 ] 3– with Raman spectroscopy. However, according to the authors knowledge, the pentachloro species has not been confirmed yet by other methods. The actual known crystal structure and spectroscopic data of solids and solution species suggest the UO 2 Cl 4 2− unit as the limiting species.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such chloro complexes in ionic liquids may have some importance for the reprocessing by partitioning and further transmutation of highly radioactive waste . Several experimental and theoretical attempts have been made to reveal U(VI) chloro complexes with higher coordination numbers than those provided in the thermodynamic database. In aqueous solution up to three U(VI) chloro complexes, [UO 2 Cl] + , [UO 2 Cl 2 ] 0 , and [UO 2 Cl 3 ] − , have been observed by EXAFS (extended X-ray absorption fine structure) and UV–vis spectroscopy. Nguyen-Trung et al indentified the species [UO 2 Cl] + , [UO 2 Cl 2 ] 0 , [UO 2 Cl] 3− , [UO 2 Cl 4 ] 2− , and [UO 2 Cl 5 ] 3– with Raman spectroscopy. However, according to the authors knowledge, the pentachloro species has not been confirmed yet by other methods. The actual known crystal structure and spectroscopic data of solids and solution species suggest the UO 2 Cl 4 2− unit as the limiting species.…”
Section: Introductionmentioning
confidence: 99%
“… ,, In contrast, the pentacoordinated complex UO 2 F 5 3− has been observed under different conditions. , [UO 2 Cl 4 ] 2− has the centrosymmetric symmetry D 4 h which is related with a characteristic vibronic UV–vis spectrum. ,,, The UV–vis absorption spectrum of the limiting species [UO 2 Cl 4 ] 2− is well understood, but structural details of the intermediate species are still under discussion. Paviet-Hartmann and Lin extracted the quantitative species distribution of [UO 2 ] 2+ , [UO 2 Cl] + , and [UO 2 Cl 2 ] 0 in aqueous solution by principal component analysis of UV–vis spectra . However, at present, the analysis of the full U(VI) chloride species distribution including the limiting species UO 2 Cl 4 2− is missing in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this correlation the species UO 2 Cl + , UO 2 Cl 2 0 , UO 2 Cl 3 - , UO 2 Cl 4 2- , and UO 2 Cl 5 3- were deduced in the concentration range 3−22 M [Cl - ]. UV−Vis spectroscopy shows significant spectral features which allowed to discriminate the species UO 2 2+ , UO 2 Cl + , and UO 2 Cl 2 0 quantitatively. , Allen et al recently investigated the structure of U(VI) complexes in aqueous chloride solutions by EXAFS spectroscopy. For concentrations up to 14 M [Cl - ], they observed the species UO 2 (H 2 O) 5 2+ , UO 2 (H 2 O) x Cl + , UO 2 (H 2 O) x Cl 2 , and UO 2 (H 2 O) x Cl 3 - with U−Cl distances varying from 2.71 to 2.73 Å.…”
Section: Introductionmentioning
confidence: 99%